A Review Article: Access Recirculation Among End Stage Renal Disease Patients Undergoing Maintenance Hemodialysis - Zeraati, Abbasali (Kowsar, 2013)
BACKGROUND: The presence of arterio-venous (A-V) fistula recirculation among hemodialysis (HD) patients markedly decrease adequacy of dialysis. OBJECTIVES: The present article summarize some of observations about clinical significance, causes, the most common techniques for measurement, and main source of pitfall in calculation of access recirculation. MATERIALS AND METHODS: A variety of literature sources such as PubMed, Current Content, Scopus, Embase, and Iranmedex; with key words such as inadequate dialysis and arterio-venous fistula access recirculation were used to collect current data. Manuscripts published in English language as full-text articles or as abstract form were included in our review study. RESULTS: Any access recirculation among HD patients should be considered abnormal and if it presents prompt investigation should be performed for its causes. There are two most common techniques for accurate assessment of access recirculation: Urea (or chemical) and nonurea-based method by ultrasound dilution technique. The most common causes of access recirculation are the presence of high-grade venous stenosis, inadequate arterial blood flow rate, close proximity, or misdirection of arterial and venous needles placement by HD staff especially in new vascular accesses due to a lack of familiarity with the access anatomy. CONCLUSIONS: The presence of access recirculation among HD patients can lead to significant inadequate dialysis thereby resulting in reducing the survival of these patients. Therefore, periodic assessment of access recirculation should be performed in HD wards.